QoS-aware secure transaction framework for internet of things using blockchain mechanism. (15th October 2019) - Guha Roy, Deepsubhra; Das, Puja; De, Debashis; Buyya, Rajkumar
Abstract: The Internet of Things (IoT) paradigm enables an enormous network with millions of connected smart things to control almost all aspect of services. In an IoT scenario, self-configured things are dynamically connected in a universal network. The small things are broadly distributed in a real world model with some essential processing capacity and finite storage. Security, privacy and reliability are the most important pillars of the IoT infrastructure. It is challenging to share personal data, highly confidential professional data over a centralized system. The infrastructure itself is capable to provide the guarantee to transmit data safely. However, a special attention for the data along with data consistency is required. Cyber attackers and hackers mostly target the centralized systems. To triumph over these types of situations we propose a security based blockchain service along with some encryption approaches for a secure communication. The encryption and decryption is performed by a hash based secret key. Risk modelling and relative risk reduction also done to prevent attacks under a virtual private network in IoT domain. Before and after attack users also wish to know quality of service (QoS). We have developed a mobile application framework which provides desire output of a user from different aspect of QoS for better understanding. The MQTT broker performs as a negotiator to convey data between cloud consumer and cloud provider. In QoS monitoring section user get chance to reconsider availability, reliability and responsibility like QoS factors while recovering resources and actual resources before attacking system based on CPU utilization, cache status and storage. As per experiment result we able to recover 100% RAM, 97.64% CPU utilization and 78.7% storage using proposed encryption and algorithm on blockchain infrastructure.